Magnetic resonance imaging of folic acid-coated magnetite nanoparticles reflects tissue biodistribution of long-acting antiretroviral therapy - Li T (Dove Medical Press, 2015)
Tianyuzi Li,1 Howard E Gendelman,1,2 Gang Zhang,1 Pavan Puligujja,1 JoEllyn M McMillan,1 Tatiana K Bronich,2 Benson Edagwa,1 Xin-Ming Liu,1,2 Michael D Boska3 1Department of Pharmacology and Experimental Neuroscience, 2Department of Pharmaceutical Sciences, 3Department of Radiology, University of Nebraska Medical Center, Omaha, NE, USA Abstract: Regimen adherence, systemic toxicities, and limited drug penetrance to viral reservoirs are obstacles limiting the effectiveness of antiretroviral therapy (ART). Our laboratory’s development of the monocyte-macrophage-targeted long-acting nanoformulated ART (nanoART) carriage provides a novel opportunity to simplify drug-dosing regimens. Progress has nonetheless been slowed by cumbersome, but required, pharmacokinetic (PK), pharmacodynamics, and biodistribution testing. To this end, we developed a small magnetite ART (SMART) nanoparticle platform to assess antiretroviral drug tissue biodistribution and PK using magnetic resonance imaging (MRI) scans. Herein, we have taken this technique a significant step further by determining nanoART PK with folic acid (FA) decorated magnetite (ultrasmall superparamagnetic iron oxide [USPIO]) particles and by using SMART particles. FA nanoparticles enhanced the entry and particle retention to the reticuloendothelial system over nondecorated polymers after systemic administration into mice. These data were seen by MRI testing and validated by comparison with SMART particles and direct evaluation of tissue drug levels after nanoART. The development of alendronate (ALN)-coated magnetite thus serves as a rapid initial screen for the ability of targeting ligands to enhance nanoparticle-antiretroviral drug biodistribution, underscoring the value of decorated magnetite particles as a theranostic tool for improved drug delivery. Keywords: folic acid, decorated nanoparticles, magnetite, theranostics, magnetic resonance imaging